Fine-Tuning of Transcription in Pichia pastoris Using dCas9 and RNA Scaffolds - Baumschabl, Michael (ACS Synth Biol, 2020)
[Image: see text] For metabolic engineering approaches, fast and reliable tools are required to precisely manipulate the expression of target genes. dCas9 can be fused via RNA scaffolds to trans-activator domains and thus regulate the gene expression when targeted to the promoter region of a gene. In this work we show that this strategy can be successfully implemented for the methylotrophic yeast Pichia pastoris. It is shown that the thiamine repressible promoter of THI11 can be activated under repression conditions using a scgRNA/dCas9 construct. Furthermore, the RIB1 gene required for riboflavin production was activated, leading to increased riboflavin production exceeding the riboflavin titers of a conventional RIB1 overexpression with a pGAP promoter.